Characterization of volatile compounds, structural, thermal and physico-mechanical properties of cross-linked polyethylene foams degraded thermo-mechanically at variable times. (December 2016) - Formela, Krzysztof; Wołosiak, Magdalena; Klein, Marek; Wang, Shifeng
Abstract: Waste cross-linked polyethylene foam (wXLPE) was thermo-mechanically degraded at variable time using internal batch mixer. The progress of wXLPE degradation has been investigated by using a simultaneous thermogravimetric/differential scanning calorimetry analyzer coupled with Fourier transform infrared spectroscopy, swelling measurements, tensile tests and scanning electron microscopy. Volatile organic compounds generated during wXLPE degradation were determined using static headspace and gas chromatography-mass spectrometry. It was observed that duration of thermo-mechanical processing of wXLPE has significant impact on content of low molecular degradation products, chemical structure, swelling, thermal and morphological properties of degraded wXLPE, while its impact on physico-mechanical properties was negligible. This indicates complex structural and chemical changes in wXLPE during its thermo-mechanical degradation, which is related to two opposite factors: (i) decrosslinking efficiency during thermo-mechanical processing of wXLPE and (ii) partial plasticization of polyethylene matrix by volatile degradation products.